The spirit of the laws : the plunder of wealth in the Armenian genocide - Akçam, Taner, 1953-; Kurt, Ümit (War and genocide, 2015)
Pertinent to contemporary demands for reparations from Turkey is the relationship between law and property in connection with the Armenian Genocide. This book examines the confiscation of Armenian properties during the genocide and subsequent attempts to retain seized Armenian wealth. Through the close analysis of laws and treaties, it reveals that decrees issued during the genocide constitute central pillars of the Turkish system of property rights, retaining their legal validity, and although Turkey has acceded through international agreements to return Armenian properties, it continues to refuse to do so. The book demonstrates that genocides do not depend on the abolition of the legal system and elimination of rights, but that, on the contrary, the perpetrators of genocide manipulate the legal system to facilitate their plans.